Cherry Blossom Forecast Based on Transcriptome of Floral Organs Approaching Blooming in the Flowering Cherry (Cerasus × yedoensis) Cultivar ‘Somei-Yoshino’ - Shirasawa, Kenta; Esumi, Tomoya; Itai, Akihiro; Isobe, Sachiko (Frontiers in Plant Science, 2022)
To gain insights into the genetic mechanisms underlying blooming and petal movement in flowering cherry (Cerasus × yedoensis), we performed time-course RNA-seq analysis of the floral buds and open-flowers of the most popular flowering cherry cultivar, 'Somei-Yoshino'. Independent biological duplicate samples of floral buds and open-flowers were collected from 'Somei-Yoshino' trees grown at three different locations in Japan. RNA-seq reads obtained from floral bud and open-flower samples collected in the current study (in 2019) and in a previous study (in 2017) were aligned against the genome sequence of 'Somei-Yoshino' to quantify gene transcript levels. Clustering analysis of RNA-seq reads revealed dynamic changes in the transcriptome, with genes in seven modules predominantly expressed at specific time points, ranging from 5 weeks before flowering to 2 weeks after flowering. Based on the identified gene modules and Gene Ontology (GO) terms enriched at different floral stages, we speculate that the genetic mechanisms underlying petal movement and flower opening in cherry involve the processes of development, cell wall organization, reproduction, and metabolism, which are executed by genes encoding transcription factors, phytohormones, transporters, and polysaccharide metabolic enzymes. Furthermore, we established a statistical model for cherry bloom forecasting, based on gene expression levels as RNA markers at different time points before flowering.